The shifting trends towards a robotically-assisted surgical interface: Clinical and financial implications. Issue 2 (June 2020) - Abitbol, Jeremie; Munir, Aqsa; How, Jeffrey; Lau, Susie; Salvador, Shannon; Kogan, Liron; Kessous, Roy; Breitner, Leslie; Frank, Russell; Kucukyazici, Beste; Gotlieb, Walter H.
Highlights: Robotics has catalyzed the shift from conventional open to less invasive surgery. The implementation of a robotics program can be a valuable investment. Continued growth in robotics research and development may further fuel surgical innovation. Abstract: Objectives: Some hospitals have invested in robotic surgery platforms to stimulate the uptake of minimally invasive surgery (MIS) and offer its benefits to more patients. The objectives were to determine the clinical and financial effects, as well as the policy implications, of a robotics program in an academic gynecologic oncology division over time. Methods: Patients treated for endometrial, cervical, and ovarian cancer within a gyn-oncology division between 2003 and 2016 were included in the current study. Clinical outcomes were described in function of surgical approach (laparotomy, laparoscopy, and robotic surgery) and tumor site. The net present value and the return on investment of the robotics program were approximated using previously reported treatment costs from our center. Results: The use of MIS soared from a high of 15% to 91% before and after the introduction of robotics in December 2007, respectively. Across all tumor sites, MIS procedures were associated with diminished blood loss and a shorter hospital stay ( p  < 0.0001). The use of robotics in gyn-oncology resulted in cost savings. Conclusions: Robotic surgery was instrumental in catalyzing the shift from open surgery to MIS and amplifying the number of patients who benefited from less invasive surgery. Continued investments in robotics and the digitization of surgery could help further drive innovation and expand its applications.